Robust finite-time output feedback control for systems with unpredictable time-varying disturbances - Wang, Huiming (2021)
This work presents a robust finite-time output feedback control method for a number of nonlinear systems that suffer unpredictable time-varying disturbances. The developed method takes advantage of control techniques based on a finite-time state observer used to estimate the lumped disturbance, where the estimator plays an important role in online compensation after being transmitted to a corresponding controller. Besides, with the state estimation provided by the finite-time state observer, the finite-time output feedback controller can guarantee the finite-time stability of the closed-loop system. The experimental results validate the effectiveness of the developed method on the trajectory tracking control of a robot manipulator.